Kajian Peluang Kerjasama Pemerintah Swasta (KPS) Dalam Penyediaan Infrastruktur di Pelabuhan Tanjung Emas Semarang - Aryani, Desy Yuli; Rahdriawan, Mardwi (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Port infrastructure in the transport system is a valuable asset for the national economy in order to face the globalization of free trade. Problems of provision of port infrastructure constraints in general is a factor financing. One of the government's efforts to overcome the problems in the provision of infrastructure financing is through the Public Private Partnership (PPP). This research was conducted in order to determine the opportunities and constraints of PPP implementation in the provision of port infrastructure by Master Plan Tanjung Emas Semarang. This study used a qualitative approach with a qualitative descriptive analysis techniques conducted on the characteristics of the PPP, the perception of government and stakeholders, as well as regulatory and institutional policies related to the implementation of the PPP. From this research it is known that in the construction and development of the port of Tanjung Emas does not currently use the PPP scheme because of the ownership status of Tanjung Emas port assets that are still in data collection, and a lack of understanding of the parties implementing the PPP. But the chances of implementing a PPP scheme is still possible in the area of ownership of assets remain below the government.